Fundamentals of industrial electronics - Wilamowski, Bogdan M.;Irwin, J. David (Boca Raton, Florida : CRC Press, 2011)
Fundamentals of Industrial Electronics is the first volume in The Industrial Electronics Handbook, Second Edition. It focuses on the fundamental areas which form the basis for the field of industrial electronics.
PART I. Circuits and signals -- PART II. Devices -- PART III. Digital circuits -- PART IV. Digital and analog signal processing -- PART V. Electromagnetics.
Includes bibliographical references and index.
Keywords: INDUSTRIAL ELECTRONICS